The Influence of Product, Price, and Location on Consumers’ Purchase Decision at Toko Kue Afifah in Pontianak City - Ahmad Parulian Siregar; Sumiyati Sumiyati (SAINTIS Publishing, 2025)
The rapid growth of the food business in Indonesia presents both opportunities and challenges for small culinary enterprises, including cake shops. This study aims to determine the influence of product, price, and location on consumers’ purchase decision at Toko Kue Afifah in Pontianak City. This research employed an associative quantitative approach with a total sample of 100 respondents selected using purposive sampling. Data were collected by doing interviews and distributing questionnaires, then analyzed using multiple linear regression with the help of SPSS 25. The results indicate that product, price, and location simultaneously have a significant influence on purchase decision; product, price, location partially has a positive and significant effect on purchase decision. These findings imply the importance of maintaining product quality, setting competitive prices, and choosing a strategic location to increase consumers’ purchase decision at Toko Kue Afifah. Future research is suggested to add other variables such as promotion, service quality, or customer loyalty to provide a more comprehensive finding.